2014
DOI: 10.1108/ijse-11-2012-0218
|View full text |Cite
|
Sign up to set email alerts
|

ICTs and maternal healthcare utilization. Evidence from Ghana

Abstract: Purpose -Traditionally, the role of technology on health services has been argued from the supply side. The purpose of this paper is to use a demand side perspective to examine the effect of Information and Communication Technologies (ICTs) on the use of maternal health services in Ghana. Design/methodology/approach -Study used data from the 2008 Ghana Demographic and Health Surveys and binary response regression models to examine the effect of women's access to ICTs on maternal healthcare utilization in Ghana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…Our findings are consistent with previous studies [16,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. This study found a strong association between ANC decision-making autonomy and women with higher education (χ 2 = 8.63, ρ = 0.035), married (χ 2 = 4.1, ρ = 0.043) and mature (36-50) (χ 2 = 8.81, ρ = 0.032); educated women were more likely to influence their decisions compared to their less educated counterparts.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with previous studies [16,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. This study found a strong association between ANC decision-making autonomy and women with higher education (χ 2 = 8.63, ρ = 0.035), married (χ 2 = 4.1, ρ = 0.043) and mature (36-50) (χ 2 = 8.81, ρ = 0.032); educated women were more likely to influence their decisions compared to their less educated counterparts.…”
Section: Discussionsupporting
confidence: 94%
“…Apart from voice services, mothers largely used their mobile phones for social media services like WhatsApp and Facebook for social interactions but not maternal issues. This relates to a similar study conducted in Ghana [27]. Although the adoption of ICT services in enhancing access and use of ANC services was still very low, which is consistent in other studies [25], a few mothers used voice, SMS and instant messages in their daily ANC routine practices with either midwives or VHT's.…”
Section: Discussionsupporting
confidence: 87%
“…It may also be the case that first-timers/women with early order birth may be responding to recommendations from health workers to use reproductive health inputs to reduce the level of risk normally associated with first-time pregnancies [ 41 ]. The negative effect on the Muslim dummy, is perhaps an indication that where beliefs associated with the Muslim religion conflict with the demands of modern medicine such as reproductive healthcare, Muslim women may opt not to use it [ 10 , 42 ]. Not surprisingly, prior authors have found that in Ghana, Muslim woman are less likely to use reproductive health inputs compared to Christian women [ 7 , 9 , 10 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Although the existing health literature on Ghana abounds in studies that have examined the determinants of reproductive health inputs [ 7 – 10 ], majority of them are either based on a single reproductive health input or on a single cross-sectional dataset. This makes it difficult to see at a glance the changes in the consumption of reproductive health inputs over time and the influence of policy-relevant covariates on several reproductive health inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake and outcomes of mHealth for pregnant women and mothers Table 4 presents the relevant themes used to develop the ICAMO model for pregnant women and mothers while Figure 4 presents a model illustrating how and why various aspects of mHealth interventions work for pregnant women and mothers. Table 4: Thematic representation of the element of pregnant women and mothers mHealth interventions also provide a communication platform for health education (I) for pregnant women and mothers [4,18,44,46,47,49,50,53,54,[58][59][60][61][62][63][64][65]. Health education is in uenced by sociocultural norms, technical aspects of mobile phone services, political clout, socioeconomic status, and community buy-in (C).…”
Section: Resultsmentioning
confidence: 99%